2018
DOI: 10.24042/ajpm.v9i2.3719
|View full text |Cite
|
Sign up to set email alerts
|

Problem Based Learning Strategy: the Impact on Mathematical Learning Outcomes viewed from Anxiety Levels

Abstract: This study aims to look at the effect of Problem Based Learning (PBL) Strategy and mathematical anxiety towards mathematics learning outcomes. The method used is the quasi-experiment method with a 2x2 factorial pattern. The data analysis technique is was the two-way analysis of variance (ANAVA) technique. This study discovers that (1) there are differences in mathematics learning outcomes between students who got the Problem Based Learning (PBL) strategy treatment and conventional learning strategies treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
1
3
0
1
Order By: Relevance
“…It means that the lower or smaller the math anxiety students have, the better the student's learning outcomes will be. The results of this study are in line with the findings of previous studies conducted by (Villamizar Acevedo et al, 2020;Asrawati, 2021;Evy Novia Nanda Artama et al, 2020) with the finding that mathematics anxiety has a negative impact on mathematics learning outcomes, so do the results (Anita, 2014) that the negative correlation between mathematics anxiety and mathematical connection ability, and the mathematics learning outcomes of students who have high anxiety levels are lower than students with the low level of achievement (Meriyati et al, 2018). Therefore, this study explains an agreement between the hypothesis and the existing data.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It means that the lower or smaller the math anxiety students have, the better the student's learning outcomes will be. The results of this study are in line with the findings of previous studies conducted by (Villamizar Acevedo et al, 2020;Asrawati, 2021;Evy Novia Nanda Artama et al, 2020) with the finding that mathematics anxiety has a negative impact on mathematics learning outcomes, so do the results (Anita, 2014) that the negative correlation between mathematics anxiety and mathematical connection ability, and the mathematics learning outcomes of students who have high anxiety levels are lower than students with the low level of achievement (Meriyati et al, 2018). Therefore, this study explains an agreement between the hypothesis and the existing data.…”
Section: Discussionsupporting
confidence: 89%
“…Astuti (2015) explains that interest is also a determinant of learning success. Several previous research results found that math interest can positively influence mathematics learning outcomes to include (Meriyati et al, 2018;Yustinaningrum, 2018;Waller, 2006).…”
Section: Introductionmentioning
confidence: 96%
“…In the learning process, students are given an LKPD that is expected to facilitate students' mathematical critical thinking skills(Agus Slamet Susanto, Haninda Bharata, 2018). In this LKPD students are required to work together with their group members, because they have to make several flat-build models then conduct experiments and measurements to answer the hypothetical results (Meriyati, Rizkia Shaulita, 2018). Then the group discusses to find the right answers from the results of their data analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Terlebih kecemasan dapat mengganggu keadaan fisik dan psikis mahasiswa tersebut. Menurut (Ardi et al, 2019;Petrowsk et al, 2020;Meriyati et al, 2018;Chardon, 2016), anxiety is a feeling of anxiety and tension in dealing with learning problems. Anxious students find learning not fun.…”
Section: Pendahuluanmentioning
confidence: 99%